(3efXheI aj GdYQhVs - (3YKeGf Hf SfO GdfLOj GdHUQj, HOQ GdOjf, GHf SfO , J (B1242 (3g` s
(3ChdgG (B:s
(3MeOJ Edgi WGYI hJPddkG ebQkG HeG CLQi Ydi hCLRdG hbGajI ef BNQ GdHjJ JfJgi dChd eG MQcJ ef bHd eG EfLdi s
(3BNQgG (B:s
(3JRa Ydi CjOi GdgHGHI fMhge dfbHS fhQ GdaVd efge hJcedG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B1s
(3GdfSNI HgG MhGTs
(3HgG Jedc HGSe YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf TjH Hf YHO GdSdGe hJGQjNI (B1294(3g`s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdeLGejYs